Assessing the potential of bus rapid transit-led network restructuring for enhancing affordable access to employment – The case of Johannesburg's Corridors of Freedom. (November 2016) - Venter, Christoffel
Abstract: Bus rapid transit (BRT) systems are often implemented as a means toward achieving regulatory reform in the transport sector. This often involves simultaneous formalisation of informal paratransit operators, and restructuring of public transport networks into centrally planned trunk-feeder systems. Such interventions might radically affect passenger access and social inclusion in ways that are as yet poorly understood. The paper uses a new accessibility metric called access envelopes to examine the potential impacts of various restructuring options on passengers' wage earning potential at job opportunities across space. The Corridors of Freedom initiative of the City of Johannesburg is used as a case study of a BRT-led restructuring exercise with land use and transport components. The study finds that it is hard to improve on the accessibility provided by the current near-ubiquitous informal minibus-taxi network. The only way that BRT implementation can improve access and affordability in the short run is by offering a fully integrated trunk with feeder services. Should such feeder services be supplied via a hybrid formal-informal approach, an integrated and progressive fare policy is critical to maintaining affordable access for poor passengers. A laissez-fare approach where taxis are allowed to provide ad hoc feeder services without any fare integration, is likely to decrease affordable access.